Role of triple phase computed tomography findings for evaluation of hepatic lesions - Ahirwar, Chandra Prakash; Patil, Abhijit; Soni, Neelam (International Journal of Research in Medical Sciences, 2017)
Background: Liver is prone to various diseases including benign and malignant because of its major function of digestion, detoxification and rich blood supply by hepatic artery and portal vein. Objectives of the study were to study the characteristic features of various hepatic lesions using triple phase CT as diagnostic modality, differentiating benign hepatic lesions from malignant and correlating findings of triple phase CT with clinical, histopathology or post-operative findings for calculation of its efficacy. Methods: A total of 100 patients were enrolled in this cross-sectional study done in Department of Radiodiagnosis, Gandhi Medical College, Bhopal, Madhya Pradesh, India. All patients underwent triple phase CECT examination and its accuracy, sensitivity and specificity was calculated. Results: Triple phase CT be excellent diagnostic modality for characterisation and better evaluation of hepatic masses with sensitivity of 91.3% , specificity 97.8% , PPV 91.3% and NPV 97.8% (p value<0.001 , kappa value 0.847). Malignant hepatic lesions can be diagnosed by triphasic CT with accuracy of 93 %, sensitivity and specificity of 93.3% and 92.5% respectively and with PPV and NPV of 94.9% and 90.2% respectively Conclusions: Triple phase CT with high accuracy is helpful in confident diagnosis of a hepatic lesion. It has an indispensible role in characterizing, evaluating and differentiating benign and malignant hepatic lesions which helps in guiding appropriate management plan with proper surgical triage. It is also helpful in reaching primary malignancy diagnosis in cases of multiple liver metastases from unknown primary.